Revealing polymerisation defects and formation mechanisms in aldol condensation for conjugated polymers via high-resolution molecular imaging - Xiaocui Wu; Stefania Moro; Adam Marks; Maryam Alsufyani; Zidi Yu; Luís M. A. Perdigão; Xingxing Chen; Alexander M. T. Luci; Callum Crockford; Simon E. F. Spencer; David J. Fox; Jian Pei; et al. (Nature Communications)
Abstract Aldol condensation is a crucial synthetic reaction in organic chemistry, particularly valued for fabricating conjugated polymers without the use of metals or toxic organostannanes. However, due to the lack of reliable and precise analytical methods, no direct evidence of the microstructure and sequence of synthesised polymers has been obtained, limiting control over their structure and performance. Here, by combining electrospray deposition and scanning tunnelling microscopy (ESD-STM), we analyse sub-monomer resolution images of four different n-type polymers produced via aldol condensation, revealing unexpected defects in both the sequence of (co)monomers and their coupling. These defects, observed across all polymer samples, indicate alternative side reaction pathways inherent to aldol condensation. Our findings not only uncover the reaction mechanism responsible for these defects but also bring new insights for the design of more effective synthetic pathways to minimise structural defects in conjugated polymers.